2009
DOI: 10.1017/s0022215109005726
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory otorrhoea: a rare case of congenital external ear salivary fistula

Abstract: Sialo-aural fistulae are extremely rare, and usually arise as a complication of surgery or as an acquired disease process. To date, only four cases have been reported. This case demonstrates the use of sensitive investigation involving sialography and computed tomography, as well as successful surgical management, with complete resolution of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The surgery was performed via a parotidectomy approach. Facial nerve monitoring was used intraoperatively, and the fistula was identified, ligated and divided using vicryl sutures [12].…”
Section: Discussionmentioning
confidence: 99%
“…The surgery was performed via a parotidectomy approach. Facial nerve monitoring was used intraoperatively, and the fistula was identified, ligated and divided using vicryl sutures [12].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 14 pathologic cases of a persistent FH reported in the literature, 11 patients were female [4][5][6][7][8][9][10][11]13,[16][17][18] . The study results may explain why most patients with a persistent FH reported in the literature were female.…”
Section: Discussionmentioning
confidence: 99%
“…The persistent FH may result in TMJ herniation and salivary fistula formation [4][5][6][7][8][9][10][11]13,[16][17][18] . It is relevant in TMJ arthroscopy, because an arthroscope may penetrate the EAC by traversing the persistent FH 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Salivary otorrhea during mastication and resultant otologic complications have been previously reported. 8,9 In our 2 patients, this dysmorphic feature served as a site of chronic infection that tracked caudally to the neck, resulted in recurrent abscesses of the parotid and submandibular areas, and later caused fistulization that mimicked a type 2 first branchial cleft anomaly. The management of the lesion is dictated by the symptoms, and in our cases, we deemed it necessary to excise the fistulous tract and diseased salivary tissue through a cervical approach given the presence of a skin fistula and the history of recurring neck abscesses that had been previously incised and drained.…”
Section: Workmentioning
confidence: 89%